Knowledge and attitude toward road traffic regulations among students of Health Sciences College in Taif Region, KSA - Ali Hassan Al-Zahrani (Universiti Kebangsaan Malaysia, 2015)
Background: Road traffic accidents (RTAs) are not frequently because of ignorance but are because of carelessness, thoughtlessness, and overconfidence, and it can lead to permanent disability. Hence, it is very important to determine the students’ attitude and knowledge toward the road traffic regulation in Saudi Arabia. Objectives: The objectives of this study were to assess the knowledge, attitudes, and practices of male students at the Health Science College in Taif University, Taif, KSA, toward road traffic regulations. Materials and Methods: This study was performed during the second semester of the academic year 2013 among the students studying at the Health Science College for Boys in Taif University, Taif, KSA. A questionnaire of 18 different questions was distributed to all available students and asked to respond under the direct supervision of the heads of the four departments of the college. The questionnaire consisted of three main parts: the first was about the sociodemographic and scientific data of the students; the second on the knowledge of road traffic regulations; and the third dealt with the attitudes of driving and the use of seat belts. Results: One hundred twenty students participated in this study. The mean age of the participants was 21 years; 30% lived in cities, and 60% and 100% had cars and driving licenses, respectively. More than half of the students had been involved in RTAs; 83.3% of these had been injured in these RTAs and 41.6% admitted to hospital for an average of 11 ± 1.3 days. High speed was the main cause of their RTAs. The percentage of knowledge of road traffic regulation was moderate in more than 90% of the students, while more than 85% of them believed in the importance of the use of seat belts. Conclusion: This study revealed that many students had been involved in RTAs as a result of driving at high speed. Most of the students had good attitude toward the use of seat belts.